1977
DOI: 10.1128/aac.12.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Netilmicin Pharmacokinetics After Single Intravenous Doses to Elderly Male Patients

Abstract: The pharmacokinetics of the new aminoglycoside antibiotic netilmicin were examined after single intravenous injections at two different dose levels to elderly male patients. The drug obeyed two-compartment model kinetics in serum, and elimination was monoexponential from 1 to 2 h after dosing. Netilmicin levels in serum were above minimum inhibitory concentration values for most susceptible organisms for up to 8 h after dosing in normal individuals and for at least 12 h in uremic patients. Urine levels of neti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 13 publications
3
15
0
2
Order By: Relevance
“…The VD ss value of netilmicin in the Obach's database (5) is 0.073 L/kg. However, the value in the original reference is 0.2 -0.3 L/kg (36) which is close to our prediction of 0.42 L/kg. An even higher value of 0.68 L/kg was announced by Wenk et al (37).…”
Section: Discussionsupporting
confidence: 89%
“…The VD ss value of netilmicin in the Obach's database (5) is 0.073 L/kg. However, the value in the original reference is 0.2 -0.3 L/kg (36) which is close to our prediction of 0.42 L/kg. An even higher value of 0.68 L/kg was announced by Wenk et al (37).…”
Section: Discussionsupporting
confidence: 89%
“…The average terminal half-life of 62.4 h is within the range determined for gentamicin by Schentag et al (25). This value is somewhat longer than that found after single-dose studies with netilmicin (17,30) and may be explained by our ability to measure serum concentrations as low as 0.02 ,ug/ml by utilizing the well diffusion assay technique. In spite of this long terminal half-life and tissue accumulation, dosing intervals of two to three times the half-life appear to be appropriate for most neonates.…”
Section: Netilmicin In Newborn Infants 251supporting
confidence: 70%
“…To our knowledge, two-compartment model pharmacokinetics have not been applied to aminoglycosides in the neonate, although there have been reports of this model for netilmicin (17,20,30), sisomicin (20), tobramycin (20), and gentamicin (3,25) in adults and older children. We analyzed the serum concentrations obtained during the steady state by both the one-and two-compartment models and found that the former model provided the best fit.…”
Section: Netilmicin In Newborn Infants 251mentioning
confidence: 99%
See 1 more Smart Citation
“…The approximate half-lives of the aminoglycosides in patients with normal renal function are: gentamicin 2-4 h (1315), tobramycin 2-3 h (2, 16), amikacin 2-4 h (2,8) and netilmicin 2-3 h (17,18).…”
Section: L I N I C a L Pharmacokineticsmentioning
confidence: 99%